Epstein–Barr Virus-Positive Langerhans Cell Sarcoma: Is There a Link? A Case Report - Guo, Yu; Zhou, Shui-Hong; Cao, Zai-Zai; Bao, Yang-Yang; Shen, Li-Fang; Yao, Hong-Tian (Frontiers in Oncology, 2022)
Langerhans cell sarcoma (LCS) is an extremely rare, malignant neoplasm that originates from Langerhans cells (LCs). Fewer than 70 cases have been reported in the English-language literature. LCS typically involves multiple organs, including the skin, lymph nodes, lungs, bone, bone marrow, liver, spleen, and soft tissues. Several etiological factors for LCS have been proposed, including immunosuppression, virus infection, and prior hematological disease. We report a rare case of LCS with Epstein–Barr virus (EBV) infection; bilateral cervical giant cysts were the initial manifestation. To our knowledge, this is the first report of LCS with EBV infection. The case information was complete, and the relevant literature was reviewed to gain insight into LCS. The case raises new questions on the oncogenic character of EBV.